The New Law of the Sea and the Greece/Türkiye Dispute in the Aegean Sea: A Disagreeable Reality Based on the Principles of the 1982 UNCLOS - MALANGU MPOSHY KASAMBULE, Daddy (Revue Internationale du Chercheur, 2025)
Abstract The new Law of the Sea of ​​1982, along with international decisions on maritime boundary delimitation, forms a framework capable of cleaving the splinter of steel that plagues the dispute between Turkey and Greece. In fact, it is difficult to argue that a legal solution is impossible, despite the contextual conditions and the geopolitical contradictions that arise on both sides between the two states. However, adding a more comprehensive approach to legal responses, in keeping with the complexity of the geopolitical context, would nonetheless be a more balanced remedy for the benefit of stability in the conflict zone. This is to say that such situations notably call for an intelligible balance between strict application of the law of delimitation and the need for common sense at the time. As it stands, the geophysical and geomorphological framework provides a basic framework for this. The objective of this article is therefore to demonstrate which of the two should dictate the proper management of the Greece-Turkish conflict in the Aegean Sea between the rigor of the law and geopolitical interests.